This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: MAS 213: Linear Algebra II. Problem list for Week #6. Tutorial on 12th October. Problem 1: (Problems 2.3.3 in [FIS].) Consider two linear transformations: • T : P 2 ( R ) → P 2 ( R ) defined by T ( p ( x )) = (3 + x ) p ′ ( x ) + 2 p ( x ). • U : P 2 ( R ) → R 3 defined by U ( a + bx + cx 2 ) = ( a + b,c,a − b ). Let β and γ be the standard ordered bases of P 2 ( R ) and R 3 . (1) Check that the expected equation [ U ◦ T ] γ β = [ U ] γ β [ T ] β holds. (2) Let h ( x ) = 3 − 2 x + x 2 ∈ P 2 ( R ). Check that the expected equation [ U ( h ( x ))] γ = [ U ] γ β [ h ( x )] β holds. Solution. We need to calculate various ingredients for this problem. First, to determine [ T ] β : • T (1) = 2 = (2) ∗ 1 + (0) ∗ x + (0) ∗ x 2 . • T ( x ) = 3 + 3 x = (3) ∗ 1 + (3) ∗ x. • T ( x 2 ) = 4 x 2 + 6 x = (0) ∗ 1 + (6) ∗ x + (4) ∗ x 2 . [ T ] β = [ T ] β β = 2 3 0 0 3 6 0 0 4 . Next, to determine [ U ] γ β : • U (1) = (1 , , 1) = (1) ∗ (1 , , 0) + (0) ∗ (0 , 1 , 0) + (1) ∗ (0 , , 1) . • U ( x ) = (1 , , − 1) = (1) ∗ (1 , , 0) + (0) ∗ (0 , 1 , 0) + ( − 1) ∗ (0 , , 1) . • U ( x 2 ) = (0 , 1 , 0) = (0) ∗ (1 , , 0) + (1) ∗ (0 , 1 , 0) + (0) ∗ (0 , , 1) . Thus: [ U ] γ β = 1 1 0 0 1 1 − 1 0 . Finally, to calculate [ U ◦ T ] γ β : • ( U ◦ T )(1) = U (2) = (2 , , 2) = (2) ∗ (1 , , 0) + (0) ∗ (0 , 1 , 0) + (2) ∗ (0 , , 1) . • ( U ◦ T )( x ) = U (3 + 3 x ) = (6 , , 0) = (6) ∗ (1 , , 0) + (0) ∗ (0 , 1 , 0) + (0) ∗ (0 , , 1) . • ( U ◦ T )( x 2 ) = U (6 x +4 x 2 ) = (6 , 4 , − 6) = (6) ∗ (1 , , 0)+(4) ∗ (0 , 1 , 0)+ ( − 6) ∗ (0 , , 1) . Thus: [ U ◦ T ] γ β = 2 6 6 0 0 4 2 0 − 6 . 1 2 So, we can finally check that the required equation does indeed hold: [ U ◦ T ] γ β = 2 6 6 0 0 4 2 0 − 6 = 1 1 0 0 1 1 − 1 0 · 2 3 0 0 3 6 0 0 4 = [ U ] γ β [ T ] β . We move on to part 2 of this problem. There are two extra pieces we need, namely: [ h ( x )] β = 3 − 2 1 and [ U ( h ( x ))] γ = [(1 , 1 , 5)] γ = 1 1 5 . Now we can check the required equation: [ U ( h ( x ))] γ = 1 1 5 = 1 1 0 0 1 1 − 1 0 3 − 2 1 = [ U ] γ β [ h ( x )] β . Tick. 3 Problem 2: (Problems 2.4.19 in [FIS].) Let T : M 2 × 2 ( F ) → M 2 × 2 ( F ) be the linear transformation which sends a matrix to its transpose. Let β be the ordered basis β = { E 11 ,E 12 ,E 21 ,E 22 } for M 2 × 2 ( F ) (where E ij is the 2 × 2 matrix which has a zero in every position except for a single 1 in the row i column j entry). Let A denote the matrix representation [ T ] β . Let M = [ 1 2 3 4 ] ∈ M 2 × 2 ( F )....
View
Full
Document
This note was uploaded on 12/08/2010 for the course SPMS MAS213 taught by Professor Andrewkricker during the Fall '10 term at Nanyang Technological University.
 Fall '10
 ANDREWKRICKER

Click to edit the document details